CLINICAL CASE OF A PATIENT WITH FAMILY HYPERCHOLESTEROLEMIA CAUSED BY MUTATION C.1859G>C (P.W620S) IN THE GENE OF HUMAN LOW DENSITY LIPOPROTEINS RECEPTOR - V. A. Korneva; T. Yu. Kuznetsova; T. Yu. Bogoslovskaya; R. Z. Murtazina; A. V. Didio; M. P. Serebrenitskaya; V. O. Konstantinov; M. Yu. Mandelshtam; V. B. Vasiliev (Кардиоваскулярная терапия и профилактика, 2015)
Clinical case of a patient with family hypercholesterolemia caused by mutation c.1859G>C (p.W620S) in the gene of human low density lipoproteins receptor.